“THE SECRET GARDEN” THE TRANSFORMATION OF A LONELY SOUL = “KHU VƯỜN BÍ MẬT” SỰ THAY ĐỔI CỦA MỘT TÂM HỒN CÔ ĐƠN - Nguyễn, Hồng Ngọc (2021)
Literature has always been a precious source of knowledge for readers in different age groups. A work can contain various moral lessons and meaningful messages that the author wish to deliver through each word. “The secret garden” is one of Frances Hodgson Burnett’s best children novels that tells the story of a little grumpy mistress and her characteristic transformation from an unpleasant child to an agreeable and cheerful one. However, Mary is not an inborn contrary and bad-temper girl. It is her parent’s indifference and callous irresponsible attitude that causes her to become a violent and impolite tyrant. After their death in a cholera disaster, Mary is sent to Yorkshire to live with her uncle and in the Missealthwaite Manor, she encountered a number of characters who assists her in discovering her true pleasant self. Since little attention was paid to the unfortunate past of Mary Lennox and the people who have significant impacts on her, this study is conducted with the aim of discussing the original cause of the child’s spoilt personalities as well as the characters who manage to awake the delightful and lively child inside of her. The researcher hopes to contribute a useful point of view as well as valuable ideas for later studies of “The secret garden”.